Prophylactic action of ayahuasca in a non-human primate model of depressive-like behavior - de Meiroz Grilo, Maria Lara Porpino; Sousa, Geovan Menezes de; Mendonça, Lilían Andrade Carlos de; Lobão-Soares, Bruno; Sousa, Maria Bernardete Cordeiro de; Palhano-Fontes, Fernanda; Araujo, Draulio Barros de; Perkins, Daniel; Hallak, Jaime Eduardo Cecilio; Galvão-Coelho, Nicole Leite (Frontiers in Behavioral Neuroscience, 2022)
Observational studies of long-term users of ayahuasca, an Amazonian psychedelic brew, seem to show an increase in resilience through improvements in emotions and cognition. In addition, ayahuasca showed clinical antidepressant action in humans and in animal studies, but little is known about its potential prophylactic action in depression. Therefore, this experimental study evaluated the potential prophylactic effects of repeated and long-term use of ayahuasca, through the modulation of resilience, in a non-human primate animal model, Callithrix jacchus, subjected to a protocol for induction of depressive-like behavior. Under this protocol, juvenile marmosets were socially isolated (IG n=5) for comparison with another isolated group being administered ayahuasca (AG n=6) and an intact (non-isolated) group that animals remained in their family (FG n=7). The AG animals received 3 administrations of ayahuasca (1.67 mL/300g of body weight) at weeks 4 (prior to isolation), 8 and 12 (both while isolated) of treatment. A more adaptive stress response was observed for the AG when compared to the IG. The AG showed higher cortisol reactivity and fecal cortisol levels than IG, while both measures were similar to FG. Moreover, AG animals showed no signs of anhedonia and no increase of chronic stress-related behaviors, which were expressed by the IG. Thus, ayahuasca seems to promote the expression of resilient responses, presenting a prophylactic action, buffering the emergence of depressive-like behaviors and cortisol alterations associated with major depression. Therefore, this study encourages research on the prophylactic use of psychedelics to prevent psychopathologies associated with chronic stress.